ANALISIS PENGETAHUAN DAN PERILAKU HIDUP BERSIH DAN SEHAT PADA MASA NEW NORMAL COVID-19 DI SDN KAPOR BURNEH BANGKALAN - Handayani, Heni Yuli (Penerbit Pendidikan Olahraga STKIP PGRI Bangkalan, 2021)
Abstract Knowledge and behavior of clean and healthy living or commonly referred to as PHBS is an effort to prevent health problems, and also as a promoter in improving health status. Related to this, especially in the new normal period, the PHBS will really feel it, as an antidote in breaking the chain of contracting COVID-19. This type of research is survey research. The sample in this study were students of SDN Kapor Burneh Bangkalan. The percentage of knowledge and behavior of students who answered correctly was 70.9% -93.7%, but most questions were answered with a presentation below 80%, this shows that the knowledge and behavior of clean and healthy living in the new normal era of COVID-19 at SDN Kapor Burneh Bangkalan is still needs to be improved.